The purchasing power parity debate - Alan M. Taylor; Mark P. Taylor (University of California, Department of Economics, 2004)
Originally propounded by the sixteenth-century scholars of the University of Salamanca, the conceptof purchasing power parity (PPP) was revived in the interwar period in the context of the debateconcerning the appropriate level at which to re-establish international exchange rate parities.Broadly accepted as a long-run equilibrium condition in the post-war period, it first was advocatedas a short-run equilibrium by many international economists in the first few years following thebreakdown of the Bretton Woods system in the early 1970s and then increasingly came under attackon both theoretical and empirical grounds from the late 1970s to the mid 1990s. Accordingly, overthe last three decades, a large literature has built up that examines how much the data deviated fromtheory, and the fruits of this research have provided a deeper understanding of how well PPP appliesin both the short run and the long run. Since the mid 1990s, larger datasets and nonlineareconometric methods, in particular, have improved estimation. As deviations narrowed between realexchange rates and PPP, so did the gap narrow between theory and data, and some degree ofconfidence in long-run PPP began to emerge again. In this respect, the idea of long-run PPP nowenjoys perhaps its strongest support in more than thirty years, a distinct reversion in economic thought.
Keywords: F31; F41; 330